Managing social risks through transitional labour markets - Klaus Schömann; Liuben Siarov; Nick van den Heuvel (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2006)
The network addressed the basic transformation of our European social and economic systems caused by globalisation, modernisation, individualisation or the shift towards the knowledge-based society. The change in the nature of social risks was one of the focal points of the project. The decline of 'old risks', inherent to an industrial society, and the advent of 'new social risks', such as life course risks or intergenerational risks, were common points of departure for the European research network. Results of the network deal with labour market processes and policy implementation. – – Das Netzwerk thematisierte die grundlegende Transformation unserer Europäischen Wirtschafts- und Sozialsysteme, die durch Globalisierung, Modernisierung, Individualisierung oder die Entwicklung zur wissensbasierten Gesellschaft verursacht werden. Das europäische Forschungsprojekt untersuchte die Veränderung in der Art der sozialen Risiken, die mehr und mehr weg von 'alten Risiken', die inhärenter Bestandteil der Industriegesellschaften waren, hin zu 'neuen sozialen Risiken', wie z.B. Lebensverlaufsrisiken oder intergenerationale Risiken. Die Ergebnisse des Netzwerks handeln von Verbesserungen von Arbeitsmarktprozessen sowie Politikimplementation.
Keywords: 330